2004
DOI: 10.3758/bf03195873
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual and perceptual information both influence melody identification

Abstract: Three processes have been identified as central to object identification: top-down processing, bottom-up processing, and lateral competition. Six experiments using the perceptual interference paradigm were conducted to assess the relative contributions of these three processes to melody identification. Significant interference was observed only when the target and the distracting information were difficult to distinguish both perceptually and conceptually. Lateral competition-the activation of specific distrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…For example, Halpern (1984) found that listeners could organize a set of familiar tunes more easily and coherently according to semantic characteristics like genre than they could according to musical characteristics like initial interval, mode, or rhythm. The large number of genre-based confusion errors observed in Experiment 2 is consistent with the pattern reported by Halpern and also supports the claim that conceptual information influences melody identification (Schulkind, 2004). That is, the data suggest that low-level perceptual information activated superordinate categorical information that the listener used to generate a response.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…For example, Halpern (1984) found that listeners could organize a set of familiar tunes more easily and coherently according to semantic characteristics like genre than they could according to musical characteristics like initial interval, mode, or rhythm. The large number of genre-based confusion errors observed in Experiment 2 is consistent with the pattern reported by Halpern and also supports the claim that conceptual information influences melody identification (Schulkind, 2004). That is, the data suggest that low-level perceptual information activated superordinate categorical information that the listener used to generate a response.…”
Section: Discussionsupporting
confidence: 79%
“…This effect is quite general, having been observed with photographic images (Bruner & Potter, 1964), line drawings (Lindfield & Wingfield, 1999;Lindfield, Wingfield, & Bowles, 1994;Luo & Snodgrass, 1994;Schulkind, 2000;Snodgrass & Hirshman, 1991), visually presented words (Peynircioǧlu, 1987(Peynircioǧlu, , 1990Peynircioǧlu & Watkins, 1986), aurally presented words (Gibson & Watkins, 1991), and aurally presented familiar melodies (Schulkind, 2000(Schulkind, , 2002(Schulkind, , 2004. Most experiments compare performance across two conditions, labeled fixed and ascending.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations